A Vote Tallying System Based on Computer Vision - Sousa, Paulo Victor Fernandes; Rodrigues, Julio Cesar da Silva; Barros, Charles Figueredo de (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2022.224595, 2022)
In this paper, we describe an ongoing project on a vote tallying system based on computer vision. The core idea consists of recording the votes into paper ballots containing markings that can be read by a software using computer vision. The software reads the markings from a video recorded during the elections. The video can be made publicly available, so that any interested party can check that the tallying is correct.